Study on the Adhesion Properties of Raw Coal and Adhesive Clogging Characteristics of Underground Coal Bunkers - Chongyang Jiang; Lianguo Wang; Zhiyuan Pan; Jiaxing Guo; Shuai Wang (Applied Sciences)
The automation and continuous operation of coal production are fundamental to the construction of high-yielding and efficient mines. Underground coal bunkers, serving as the pivotal link between various production and transportation segments, are vital for the seamless operation of mines. Nonetheless, the adhesive properties of raw coal can lead to increasingly severe issues, such as the adhesive clogging of coal bunkers. To address this issue, this paper first employs a self-designed raw coal shear testing apparatus to conduct experiments under varying conditions of shear interfaces, moisture content in raw coal, and compaction forces. Obtaining the adhesion behavior characteristics and adhesion parameter variation patterns of raw coal at coal-coal and coal-wall interfaces under various influencing factors. Subsequently, leveraging the adhesion property parameters of raw coal and the engineering conditions of the 1011 roadway coal bunker in Taoyuan Coal Mine II, a numerical model for coal bunker discharge using irregular particles was developed with the PFC2D numerical simulation software. Based on these, we obtained the influence patterns of various factors, such as coal bunker convergence angle, coal storage height, and coal moisture content, on the coal particle flow pattern, bunker wall pressure, and adhesive clogging distribution characteristics of the coal bunker during the discharge process, thereby revealing the mechanisms underlying the adhesive clogging phenomenon. The findings offer significant insights for optimizing solutions to the adhesive clogging issues in underground coal bunkers and ensuring their safe and efficient operation.